Impact of Meteorological Conditions on Airborne Particulates (PM2.5 & PM10) Concentration on Universiti Tun Hussein Onn Malaysia (UTHM) Ambient: Humidity - Thomas, Whitney; Mat Daud, Azra Munirah (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
The goal of this study at Universiti Tun Hussein Onn Malaysia is to determine the impact of meteorology on the concentration of airborne particulates in the ambient air. Air pollution is becoming more of a problem as a result of unregulated chemical gas emissions from industry, fossil fuel combustion, and forest fires. Air quality in UTHM ambient shall be considered carefully as it will give unsatisfactory comfort level and affecting the health of the occupants in UTHM as there are various human activities contribute to air pollution at UTHM ambient air. In this study, the concentration of particulate matter in UTHM air ambient are measured using Met One E – Sampler and the Meteo Compact Station to collect data on particulate matter and meteorological conditions such as wind speed, relative humidity, and temperature and were used to compared the data collected from both stations. A total of 14 days of data were gathered at Faculty of Civil Engineering and Built Environment (FKAAB) and Makmal Kejuruteraan Bahan Termaju (FKAAB). COMET software was used to retrieve the data from Met One E-Sampler, meanwhile the data from Meteo Compact Station can be retrieve from Delta Ohm Cloud website after instrument is set up. However, in this study, the data was provided by FKAAB Building Services and Maintenance Cluster. The concentration measured may be generated by surrounding human activity such as manufacturing plants, construction, heavy traffic, and other human activities. From the study, the result that shows the greatest average levels of PM10 and PM2.5 were found in Makmal Kejuruteraan Bahan Termaju (FKAAB), with 33.21 µg/m3 and 29.0 µg/m3, respectively. However, both stations’ particulate concentrations are below the New Ambient Air Quality Standard (NAAQS). Future research should focus on determining the most significant human activities that contribute to the presence of contaminants in the ambient air at UTHM by using instruments that can collect various data at the same time, such as the Meteo Compact Station. This enables data to be collected and compared simultaneously. Other than that, the relevant parties or university must take action by developing more solutions for reducing society’s exposure to airborne particles and improving UTHM’s air quality to ensure that their comfort and health do not deteriorate.